SDG15 - life on land : towards effective biodiversity management - Ansari, Nasim Ahmad; Agus, Cahyono; Nunoo, Edward Kweku (Concise guides to the United Nations Sustainable Development Goals., 2021)
This book, the first of its kind, seeks to demonstrate how 'SDG15 - Life on Land' can be implemented through effective biodiversity management, mainstreaming strategies and proposing solutions to achieve and consolidate the goals. The book will be of great interest to natural resource policy makers, scholars and students of natural resources, development studies and sustainable development, as well as those engaged in international climate change discourse and non-government organisations. Drawing on experienced faculty scientists who are experts in natural resource governance issues in a wide variety of fields ranging from forestry, biodiversity conservation policy to climate change, this work proposes solutions to achieve and consolidate SDG15. Delving into SDG15 targets and indicators, drawing on examples from across the regions to give a truly global policy perspective, and understanding the significance of the forest ecosystem as the foundation for sustainable development, the authors demonstrate how SDG15 can and will be an appropriate tool for mainstreaming biodiversity across the policy sectors of governance. Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.